ASSISTANCE OF VARIOUS FOOD PROCESSING ACTIVITIES BASED ON LOCAL POTENTIAL IN PKK GROUP RUKURAMBA VILLAGE, ENDE-NTT - Raji, Manggu Ngguna; Sariyyah, Nining; Wangge, Yuliani Sepe (Journal of Islam and Science, 2019)
This activity aims to provide an understanding to the Rukuramba village PKK group regarding food processing based on local potential. The activity was carried out for one day using the method of socialization and workshop. The results of the activities showed that there was an increase in participants' understanding of food processing based on local potential. As for food products produced in the form of cassava noodles, merungge noodles, fish balls, and fish crackers